Triggering Turbulence: How Trump’s Tariff Talk Shook the Markets - Riyono, Kenley Maccauley; Stanley, Nicklaus; Easter, Rafael Savio; Adijaya, Vincent; Purnomo, Ruben Putranto; Widianingsih, Luky Patricia (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2026)
On April 2, 2025, President Donald J. Trump imposed a 32% import tariff on Indonesia, triggering significant stock market volatility and global panic. This study aims to provide empirical evidence on whether there are significant differences in aggregate and cumulative abnormal returns before and after Trump’s reciprocal tariff policy announcement. The research adopts an event study approach, using a sample comprising all companies across 11 sectors listed on the Indonesia Stock Exchange. The findings indicate that the Indonesian capital market responded negatively and significantly to Trump’s tariff announcement. This is reflected in a significant decline in the Aggregate Abnormal Return (AAR) on the first day following the announcement. The decline is also evident in the Cumulative Aggregate Abnormal Return (CAAR), which illustrates the aggregate market losses accumulated during the event window. However, the drop in AAR and CAAR lasted only for two days post-announcement, after which signs of recovery emerged from the third to the fifth day. Further analysis of sectoral Abnormal Returns (AR) shows that most sectors closely linked to international trade activities experienced a significantly negative decline in AR.